Do the macroeconomic indicators influence foreign direct investment inflow? Evidence from India - Akhil SHARMA; Abdul RISHAD (Theoretical and Applied Economics, 2020)

(untitled)
This study significantly contributes to the growing literature on the dynamic link between FDI inflow and macroeconomic factors like inflation, trade openness, market size, and exchange rate in the case of India. An Autoregressive Distributed Lag bound testing approach with annual time-series data from 1975 to 2017 employed for modelling the short-run and long-run dynamics. Using Wald coefficients, the study found integration between the variables. It further discovered that variables are correcting the shock-induced disequilibrium at a speed of 86%. In the long-run trade openness and real gross domestic product positively affect the FDI inflow, whereas the exchange rate and inflation are negatively associated with FDI inflow. However, the study failed to detect any short-run association among the variables. Based on the findings, the research suggests better management of inflation and exchange rate volatility through specific policy action for attracting more global capital to the economy.